Synthesis and HPLC resolution of isomers of novel phosphorus fluorinated 2,4,6-trimethylphenylazo pyridines - Hacini, Zineb; Sekhri, Lakhdar (European Journal of Chemistry, 2016)
New compounds of phosphorus fluorinated 2,4,6-trimethylphenylazo pyridines (4a-c) have been synthesized in high yields via adding n-butyl lithium in hexane to a stirred solution of methyldiphenylphosphine oxide in dry THF at 0 °C, then cooled to around -78 °C, treated with azo-pyridines(2a-c) and then allowed to warm at room temperature over 2 h. The isomers of (E)-((5-chloro-3,6-difuoro-4-(mesityldiazenyl)pyridin-2-yl)methyl)diphenyl phosphine oxide (4b) and (E)-((3,6-difuoro-4-(mesityldiazenyl)5-methoxypyridin-2-yl)methyl)diphenyl phosphine oxide (4c) can be separated on analytical HPLC: Chiralcel OD-H column, hexane:2-PrOH, (9:1, v:v) mobile phase, flow-rate, 1.0 mL/min, 25 °C, λ = 254 nm and polarimetric detection, 20 µL injection volume. The resolution of this isomers were 2.12, 1.84, respectively.